(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Purpose. To analyze surgical treatment results of concomitant strabismus (CS) patients based on volume of operation preliminary modeling using three-dimensional biomechanical eye model (TBEM). Material and Methods. There were analyzed surgical treatment results in 106 patients with CS, which were operated on after volume of operation was preliminary modeled at TBEM«SEE-KID». Results. Orthotropy was obtained in 54/106patients (50,9 %) at the first day postoperatively. 52/106patients (49,1 %) had residual angle of 5—10° — hypocorrection was in 44 patients, and hypercorrection was in 8 patients. 18patients were lost to follow-up. At 3—12 months follow-ups ortothropy has been preserved in 53/88 patients (60,2 %), and in 35/88patients residual angle of 5—10° remained — hy-pocorrection was in 31 patient, and hypercorrection was in 4 patients. Conclusion. TBEM use in complex examination and treatment of CS patients allows prognosing surgery result in 60 % of cases and accelerates diagnostic process, but the method needs further investigation. Particularly, extraocular muscles bio-mechanics needs to be more precisely estimated (degree of the muscle hyper- or hypofunction, movement amplitude).